2010
DOI: 10.1103/physrevb.82.054406
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from superspin glass to superferromagnet inFexAg100xnanostructured thin films

Abstract: Fe x Ag 100−x granular thin films, with 20Յ x Յ 50, have been prepared by the dc-magnetron sputtering deposition technique. With this technique we have been able to obtain samples comprising small Fe nanoparticles ͑2.5-3 nm͒ embedded in a Ag matrix, remaining their size practically constant with increasing Fe content. Their magnetic behavior has been fully characterized by dc magnetic measurements between 5-350 K. They have revealed a crossover in the collective magnetic behavior of the Fe nanoparticles around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 31 publications
11
72
0
Order By: Relevance
“…These properties in thermomagnetic ZFC/FC curves are associated with a ferromagnetic behavior. [15][16][17][18][19]28 A similarly shaped ZFC curve, as a result of strong ferromagnetic correlations between particles, has also been observed by Sousa et al 28 in granular CoFe=Al 2 O 3 multilayers and by JimenezVillacorta et al 19 in Fe/Si 3 N 4 multilayers. Hansen et al…”
Section: B Magnetic Properties Of Pristine Fe Nanoparticles and Fe@ssupporting
confidence: 62%
See 2 more Smart Citations
“…These properties in thermomagnetic ZFC/FC curves are associated with a ferromagnetic behavior. [15][16][17][18][19]28 A similarly shaped ZFC curve, as a result of strong ferromagnetic correlations between particles, has also been observed by Sousa et al 28 in granular CoFe=Al 2 O 3 multilayers and by JimenezVillacorta et al 19 in Fe/Si 3 N 4 multilayers. Hansen et al…”
Section: B Magnetic Properties Of Pristine Fe Nanoparticles and Fe@ssupporting
confidence: 62%
“…15,16 Bedanta et al 16,17 reported the suppression of dipolar disorder among the superspins in dense CoFe nanoparticle ensembles leading to the long-range ordered SFM state. Similarly, Alonso et al 18 observed the crossover from SSG to SFM behavior in FeAg thin films. At lower concentrations of Fe nanoparticles, a collective freezing of the magnetic moments was observed; whereas at higher concentrations, direct exchange interactions were present between Fe nanoparticles.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…6. The progressive freezing of magnetic moments of the interacting nanoparticles increases the irreversibility between ZFC and FC [1,32,33]. The magnetic relaxation in such systems is dominated by the strength of dipolar interparticle interactions Ed and they can exhibit a range of behaviors from superspin glasses to superferromagnets with increasing Ed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if the composite is made of insulating magnetic nanoparticles, direct exchange does not lead to finite simple electrical conductivity of the composite. If the particles concentration is reduced to avoid physical contact, then different types of interactions that can influence the collective magnetic behavior are; tunneling, RKKY interaction in the case of a composite with non-magnetic metallic medium separating the magnetic nanoparticles and simple dipole-dipole interactions [1][2][3]. Hence it can be seen that collective behavior of single domain magnetic nanoparticles is a strong function of their concentration as well as their spatial arrangement.…”
Section: Introductionmentioning
confidence: 99%